Remote Sensing for Agriculture, Ecosystems, and Hydrology XXI 2019
DOI: 10.1117/12.2532564
|View full text |Cite
|
Sign up to set email alerts
|

Landscape changes at Chernobyl

Abstract: Thirty-two years ago, the Chernobyl nuclear accident changed the lives of many people, when one of the nuclear reactors exploded during a safety test. The explosion released huge amounts of radioactive materials like caesium, strontium, and plutonium into the atmosphere. High doses of radiation caused severe damage to the DNA of living beings, with direct impact on the changes suffered by the environment, either by causing instant death or by altering the fitness of the local biota. As people were evacuated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…A general outcome is the surprising resilience of plants and animals to chronic exposure to radiation. The results of the present study are in agreement with the findings of [30,31], that both showed an increase in NDVI values long after the accident, while they highlighted that humanity still has not yet reached a full understanding of the consequences of the Chernobyl nuclear accident. An explanation of the remarkable resilience of plants comes from [58], explaining the various mechanisms of plants to replace dead cells or tissues easier than animals, irrespective of the source of damage, i.e., due to attack by an animal or due to radiation.…”
Section: Discussionsupporting
confidence: 93%
“…A general outcome is the surprising resilience of plants and animals to chronic exposure to radiation. The results of the present study are in agreement with the findings of [30,31], that both showed an increase in NDVI values long after the accident, while they highlighted that humanity still has not yet reached a full understanding of the consequences of the Chernobyl nuclear accident. An explanation of the remarkable resilience of plants comes from [58], explaining the various mechanisms of plants to replace dead cells or tissues easier than animals, irrespective of the source of damage, i.e., due to attack by an animal or due to radiation.…”
Section: Discussionsupporting
confidence: 93%
“…The Chernobyl Exclusion Zone is characterized by predominant cover with grasses and trees following the impact of the nuclear disaster. Santos et al (2019) used the Normalized Difference Vegetation Index (NDVI) derived from satellite images and measurements of ambient radiation from the ground. Remote sensing and Landsat satellite images across years were used to relate NDVI to background radiation.…”
Section: Effect Of Ionizing Radiation On Plant Ecosystemsmentioning
confidence: 99%
“…The Chernobyl Exclusion Zone is now dominated by grasses and shrub/trees with the latter dominated by Scots pine and silver birch Betula pendula. Santos et al (2019) concluded that there were positive effects of abandonment of farmland for the abundance of some plant species, while there were negative impacts of exposure to ionizing radiation on the vegetation. Finally, Santos et al (2019) showed that the vegetation was negatively affected by a threshold level of ionizing radiation.…”
Section: Effect Of Ionizing Radiation On Plant Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations